The health support arrangement experience of the XXII Olympic winter games and XI Paralympic winter games 2014 in Sochi - E. F. Philippov; T. Y. Kobrinyuk (Кубанский научный медицинский вестник, 2015)
The article describes the experience of the health support arrangement by the ministry of health of the Krasnodar region in the period of preparation and holding of the XXII Olympic winter games and XI Paralympic winter games 2014 in Sochi. Data on appeals for medical care in all health institutions and offices providing medical assistance to the participants and guests of the Olympic winter and Paralympic winter games are also given. The specifics of medical care and especially medical evacuation are described.